IJIME DI TEMPAT KERJA, KESEHATAN MENTAL, DAN RISIKO JISATSU: ANALISIS KRIMINOLOGIS PADA VIKTIMISASI PEKERJA DI SHIBUYA STATION JEPANG - Dhea Aprilia Ananda; Eka Putri Tungga Devi; Ahmad Sulthoni (CV. Lafadz Jaya, 2026)
This article analyzes the relationship between workplace ijime, workers mental health, and the risk of jisatsu from a criminological-victimological perspective. The discussion is situated in the workplace context around Shibuya Station, Japan, an urban working space characterized by service intensity, hierarchical relations, rapid work rhythms, and strong expectations of social harmony. This study applies a qualitative literature review by examining scholarly works on workplace bullying, power harassment, mental health, suicide, and relevant criminological theories. The findings indicate that workplace ijime can be understood as psychological violence operating through humiliation, exclusion, intimidation, excessive pressure, and abuse of power relations. This process places workers in situations of primary and secondary victimization, increasing their vulnerability to anxiety, depression, loss of self-esteem, emotional exhaustion, social isolation, and helplessness. The novelty of this article lies in framing ijime as a criminological issue within the workplace rather than merely an individual psychological problem. Prevention should therefore strengthen organizational social control, safe reporting mechanisms, victim protection, psychosocial support, and an anti-violence work culture.